Front Matter - Araujo, Renata; Siqueira, Sean (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2021: Anais do XVII Simpósio Brasileiro de Sistemas de Informação, 2021)
Front Matter SBSI 2021.